Félix Guattari : an aberrant introduction - Genosko, Gary (Continuum, 2002)
This is a detailed assessment of the life and work of Felix Guattari, "Mr Anti" as the French press labelled him, the friend of and collaborator with Gilles Deleuze, Jacques Lacan and Antonio Negri, and one of the 20th century's last great activist-intellectuals. Guattari is widely known for his celebrated writings with Deleuze, but these writings do not represent the true breadth and impact of his thinking, writing and activism. Guattari's major work as a clinical and theoretical innovator in psychoanalysis was closely linked to his participation in struggles against European right-wing politics. This book introduces the reader to the diversity and sheer range of Guattari's interests, from anti-psychiatry, to Japanese culture, political activism and his theorizing of subjectification.